STUDENTS’ PERCEPTION ON THE USE OF QUIZIZZ AS ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Muhammad Khoerul Hadist (STKIP Muhammadiyah Bogor, 2022)
The objectives of this research is to describe the students' perceptions, and to find out the obstacles that students face in using Quizizz as online learning during the COVID-19 Pandemic. This study was designed a descriptive qualitative. The participants of this research are 25 students at the eight grade of SMPN 1 JASINGA. The participants of this research were selected using purposive sampling technique. The data were obtained through distributing questionnaires to the participants. The results of this study had shown the students’ perception on the use of Quizizz as online learning during the Covid-19 at SMPN 1 JASINGA had a positive perception based on the variables such as; attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty.